Expanding the Theoretical Framework in Student Debt Research by Connecting Public Policy Theories to the Student Debt Literature - Mbah, Ruth Endam (Advances in Social Sciences Research Journal, 2021)
Current changes in the economic atmosphere have severely impacted the higher education sector worldwide. Policymakers worldwide are facing the challenge of adjusting tuition and financial aid programs in response to these changing economic times. The shift from federal grants to loans has caused student loans to be a popular means of funding higher education for most low and medium-income families. A result of this, is the increase in student loan default as most college students graduate with unmanageable debts, thus, a rising concern for policymakers. The purpose of this paper is to link four public policy theories (Social Contract Theory, Utilitarian Theory, Theory of Neoliberalism, and Three-Policy Stream Theory) to student loan literature. This is to expand the limited database of public policy theories in student loan debt literature. This theoretical linkage points out the role of policymakers in (1) ensuring the security of lives and the preservation of the property of those who voted them into power (Social Contract Theory); (2) establishing educational policies that ensure the ‘the greatest happiness of the greatest number’ (Utilitarian Theory); (3) upholding social welfare or a ‘welfare state’ through fiscal and monetary policies to ensure high employment rates for graduates, low inflation and the provision of public goods (Theory of Neoliberalism), and (4) the risk of undermining the growing power of an informal interest group that is made up of millennials saddled with student loan debt (Three-Policy Stream). These theories reiterate the principal role of policymakers in enhancing human capital through affordable education.